Distributions fractales des Pistes de Ski et des Remontées Mécaniques. Exemple de la station de Serre Chevalier - Ivan Brissaud (Unité Mixte de Recherche 8504 Géographie-cités, 2007)
The analysis of the ski lift and of the ski slope distributions, is performed in the case of the Serre Chevalier resort. First, we show that the number and the rate of building of this equipment follow logistic equations over a 50 years period. Rank-size curves show some hierarchies of lift characteristics. Using the Fractalyse code, we confirm that the spatial distribution of the two networks – approximated to an invariant scale system- is relevant to fractal geometry. The values of the fractal dimensions depend on the opportunities of the lifts, of the difficulties of the slopes, and of the distribution of the two networks. Some conclusions could be deduced from these results to characterize the ski resorts.